AKTUALISASI NILAI-NILAI DASAR PROFESI PEGAWAI NEGERI SIPIL DI KANTOR IMIGRASI KELAS I TANJUNG PRIOK TENTANG LAYANAN PENGADUAN DALAM PERMOHONAN PENERBITAN PASPOR - Afif Alamsyah Makarao (VERITAS, 2018)
This actualization is prepared in order to fulfill the task of Latsar Group III ofclass V. The actualization design is also expected to be used as a guide in theimplementation of government employees (ASN) basic values actualizationactivities during the implementation of Basic Training upon return to theirrespective work units. The issues to be faced are as follows: 1. There are stillpeople coming to the Immigration Office to complain about the passport issuanceservice. So the authors assume that the dissemination of information about theservice of the passport issuance is not yet optimal. 2. There are still people who donot understand about the numbering and additional procedures in the passportissuing queue. So the authors assume that there is still need additional informationabout ordering the queue. 3. Still not optimal record in entry process and scannerverification file of passport issuance application. So it is difficult to know thenumber of passports that will and have been processed in 1 day.